2020
DOI: 10.2174/1871520620666200408082026
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-Mediated Apoptosis and Cellular Senescence in Human Colon Cancer

Abstract: Background: Quercetin is a flavonol from the flavonoid group of polyphenols which positively affects human health due to its anti-cancer, anti-inflammatory, anti-microbial and cardioprotective effects. The effects of phenolic compounds, including quercetin, on programmed cell death and cellular senescence have been the subject of research in recent years. Objective: In this study, we aimed to investigate the effects of quercetin on cell viability, apoptosis and cellular senescence in primary (Colo-320) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The most prominent results were acquired at the highest concentration of 50 µM ( Figure 6 ) when specific senescence features such as increased cell size, and elevated senescent-associated beta-galactosidase (SA-β-gal) expression [ 44 ] highlighted by a dark coloration within the cell cytoplasm were detected. Our results are endorsed by previous studies that reported the capacity of several natural bioactive compounds (e.g., curcumin, quercetin) to force cancer cells to undergo senescence in vitro [ 45 , 46 , 47 ]. Multiple mechanistic pathways have been attributed to the pro-senescence effect of natural polyphenols in cancer cells, including modulation of tumor suppressor or oncogene gene expression, DDR (DNA damage response) activation, ROS generation, promotion of endoplasmic reticulum (ER) stress, and regulation of epigenetics [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
“…The most prominent results were acquired at the highest concentration of 50 µM ( Figure 6 ) when specific senescence features such as increased cell size, and elevated senescent-associated beta-galactosidase (SA-β-gal) expression [ 44 ] highlighted by a dark coloration within the cell cytoplasm were detected. Our results are endorsed by previous studies that reported the capacity of several natural bioactive compounds (e.g., curcumin, quercetin) to force cancer cells to undergo senescence in vitro [ 45 , 46 , 47 ]. Multiple mechanistic pathways have been attributed to the pro-senescence effect of natural polyphenols in cancer cells, including modulation of tumor suppressor or oncogene gene expression, DDR (DNA damage response) activation, ROS generation, promotion of endoplasmic reticulum (ER) stress, and regulation of epigenetics [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
“…Quercetin treatment reduced cell viability and induced apoptosis in primary and metastatic colon adenocarcinoma cell lines [407]. Quercetin dose-dependently suppressed HGF-and TGFα-induced migration of hepatocellular carcinoma cells by inhibiting the signaling pathway of AKT, but not p38 MAPK [413].…”
Section: Quercetinmentioning
confidence: 95%
“…hyperlipidemic rats, Q pretreatment before I/R injury increased myocardial infarct size and release of lactate dehydrogenase and creatine kinase-MB [32]. On the other hand, Q upregulated p16 expression in colon adenocarcinoma cell lines, causing cell cycle arrest and thereby preventing proliferation of cancer cells [33]. Speculatively, the increase of p16 in HQ might arrest fibroblast cells proliferation and thereby decrease cardiac fibrosis.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 97%